Where were the Jews in the development of sciences in medieval Islam? A quantitative analysis of two medieval Muslim biographical notices - Hassan, Mohammad Hannan (Hebrew Union College annual / Jewish Institute of Religion, 2010)
The period between the eighth and eleventh century witnessed active interaction and participation of both Christians and Muslims, either through the transmission of Greek sciences to the Islamic-Arabic world, or by the creative and original works of its scholars. This begs the question: Where were the Jewish scholars during this period of transmission and development of scientific disciplines in medieval Islam? Rosenthal asserts that almost all translators were Christians of various churches, with the doubtful exception of the eighth-century Jew Māsarjawayh. Salo Baron argues that "in the Caliphate's 'melting pot' of Western and Eastern science and the ensuing rapid scientific advances during the eighth and ninth centuries, Jews injected a few ingredients of their own." But how few is this few? The number of Jews participating either in the transmitting of foreign sciences (Greek, Persian or Indian) or in the form of original works during the said period is, at least numerically, insignificant. Significant Jewish contribution started only after the eleventh century, particularly in the Islamic West, motivated by the Islamic scientific discourse. I survey two medieval Muslim biographical dictionaries, Ibn Nadīm's (d. 987) Fihrist and Ibn Abī Uṣaybiʿah's (d. 1269) ʿUyūn al-Anbāʾfī Ṭabaqāt al-Aṭibbāʾ. The analysis is corroborated by another tenth-century scholar al-Masʿūdī (d. 957) and the thirteenth-century scholar al-Qifṭī (d. 1248).